PENGARUH LIKUIDITAS OBLIGASI TERHADAP PERUBAHAN HARGA OBLIGASI KORPORASI PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Firda Mufidah; Mike Mega Rahayu; Yosa Tidar Priyanto (Jurnal Studia Akuntansi dan Bisnis (The Indonesian Journal of Management & Accounting), 2021)
An investor can invest by choosing one of the securities in the capital market. The capital market in Indonesia has a variety of securities that can be used as investments. The type of alternative securities that can be used as an investment is bonds. This study aims to determine the effect of Bond Liquidity variables on Changes in Corporate Bond Prices of Banking Companies Listed on the Indonesia Stock Exchange. The period used in this study is 3 years, starting from 2016 to 2018. The population used in this study is 43 banking company bonds listed on the Indonesia Stock Exchange for the 2012-2014 period. The sample selection technique uses a purposive sampling method and 10 company bonds are used as samples. The data analysis technique used is simple linear regression and data processing using SPSS v.20. The results of the Bond Liquidity and Bond Price Change results get the calculation of adjusted R2 value of 0.026 x 100% = 2.6% means that the variable Change in Obligation Price can be explained by the independent variable Liquidity of the Bond while the rest (100% - 2.6% = 97 , 4%) is influenced by other factors not examined in this study such as Bond Coupons, Maturity Period, Curret Ratio, Leverage and so forth. Then the results of the statistical test t for the variable Liquidity Bonds have a tcount ttable ie -1.332 2.04841 with a significance level of 0.195 0.05, this means that H0 is accepted and H1 is rejected. So the results of this study are the Bond Liquidity has no effect against Changes in Bond Prices.